2019
DOI: 10.5430/css.v5n1p27
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex administration shortens reversal times but not operating room turnover times

Abstract: Objective: Current literature debates whether administration of sugammadex translates into a higher operating room (OR) efficiency when compared to neostigmine. This study is a blinded assessment of the effects of sugammadex versus neostigmine on OR efficiency as determined by time of reversal to time of the next case.Methods: 50 patients undergoing abdominal surgery were randomized and evenly distributed into two groups, one receiving sugammadex (4 mg/kg) and the other, neostigmine (0.06 mg/kg) plus glycopyrr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…4,[8][9][10] We have previously demonstrated, however, that when providers are blinded to the reversal agent, the use of sugammadex or neostigmine results in a similar OR turnover time and comparable discharge readiness from the PACU. 11 Similarly, Chae et al 12 measured nearly identical PACU stay times following sugammadex (50.0 ± 24.5 minutes) or acetylcholinesterase inhibitor (49.3 ± 20.5 minutes) reversal for colorectal surgery (P = 0.821), although this was a retrospective study. 12 A randomized controlled trial involving 100 laparoscopic hysterectomy patients revealed no significant difference in PACU stay times after sugammadex versus neostigmine reversal (sugammadex: 47.75 ± 31.77 minutes vs neostigmine: 53.43 ± 40.57 minutes; P = 0.543).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…4,[8][9][10] We have previously demonstrated, however, that when providers are blinded to the reversal agent, the use of sugammadex or neostigmine results in a similar OR turnover time and comparable discharge readiness from the PACU. 11 Similarly, Chae et al 12 measured nearly identical PACU stay times following sugammadex (50.0 ± 24.5 minutes) or acetylcholinesterase inhibitor (49.3 ± 20.5 minutes) reversal for colorectal surgery (P = 0.821), although this was a retrospective study. 12 A randomized controlled trial involving 100 laparoscopic hysterectomy patients revealed no significant difference in PACU stay times after sugammadex versus neostigmine reversal (sugammadex: 47.75 ± 31.77 minutes vs neostigmine: 53.43 ± 40.57 minutes; P = 0.543).…”
Section: Discussionmentioning
confidence: 97%
“…As a selective encapsulator of steroidal neuromuscular blocking agents, sugammadex operates with a distinct mechanism of action that reverses NMB more rapidly and effectively than traditional acetylcholinesterase inhibitors 4,8–10 . We have previously demonstrated, however, that when providers are blinded to the reversal agent, the use of sugammadex or neostigmine results in a similar OR turnover time and comparable discharge readiness from the PACU 11 . Similarly, Chae et al 12 measured nearly identical PACU stay times following sugammadex (50.0 ± 24.5 minutes) or acetylcholinesterase inhibitor (49.3 ± 20.5 minutes) reversal for colorectal surgery ( P = 0.821), although this was a retrospective study 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations